Réponses

2012-12-15T18:25:09+01:00

j'ai juste la réponse du premier exercice !!

1) B=(3x+1) (6x-9)-(2x-3)²

     B=18x²-27x+6x-9-4x²-12x+9

     B=14x²-9

 voilà!!

2012-12-15T18:44:28+01:00

Bonjour,

 

1)

B = (3x+1)(6x-9)-(2x-3)² =

 

B =18x²-27x+6x-9-(4x²-12x+9 ) =

 

B =18x²-27x+6x-9-4x²+12x-9 =

 

B = 14x²-9x-18

 

2)

(6x-9) = 3(2x-3)

 

B = 3(3x+1)(2x-3)-(2x-3)² =

 

B = (2x-3)(3(3x+1)-(2x-3)) =

 

B = (2x-3)(9x+3-2x+3) =

 

B = (2x-3)(7x+6)

 

3)

si B = 0 

 

(2x-3)(7x+6) = 0

 

(2x-3) = 0     2x = 3   x = 3/2

 

(7x+6) = 0    7x = -6  x = -6/7